Implementasi Work-Life Balance dalam Meningkatkan Kinerja Karyawan di Kelurahan Putat Gede Kecamatan Sukomanunggal Kota Surabaya - Marhaeningtyas, Suci; Puspita Ningrum, Febyana; Diyanti Cahyarini, Echa; Amaliyah; Dimisqiyani, Erindah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
The company's operational activities cannot run smoothly and well without being supported byqualified human resources. Humans are social creatures where human life does not only interactin the world of work. However, the digital era has changed the order of human life to be fast-pacedand complex. This, without realizing it, has an unfavorable effect on the lives of employees.Increasing work demands are the cause of employees having inadequate psychological health. Thepurpose of this research is to find out the implementation of work-life balance which is expectedto support the performance of employees. The research method used is a qualitative method withinterview techniques and the use of literature studies as a supporting reference. The results of thisstudy indicate that the implementation of work-life balance in Putat Gede Village is still notoptimal. This research recommends policies that better support work-life balance to improveemployee performance in the form of the use of technology in community services and policymaking that supports the implementation of work-life balance in the workplace, complementingthe workplace with facilities to relax employees, providing additional leave to employees, andimplementing rest hours during the day in order to maintain employee productivity